Asymmetrical influence of inflation variables, industrial production index, return on assets on corporate sukuk and sbsn - Mutiara Rahma; Jaka Sriyana (Institute of Computer Science (IOCS), 2024)
This research examines the influence of inflation factors, industrial production index (IPI) and return on assets (ROA) on corporate sukuk and SBSN. This research takes the form of time series data originating from the Financial Services Authority (OJK), Bank Indonesia (BI) and the Central Statistics Agency (BPS) from monthly data, namely from January 2011 to December 2022. The analysis method in this research uses a non-linear model. Autoregressive Distributed Lag Model (NARDL). The research results show that in the long term the inflation variable has a symmetrical effect on corporate sukuk and an asymmetrical effect on SBSN. Meanwhile, in the short term, inflation has no effect on corporate sukuk or SBSN. In the long term, the Industrial Production Index variable has an asymmetrically significant effect on SBSN but has no effect on corporate sukuk. Meanwhile, in the short term, IPI has a symmetrically significant effect on corporate sukuk and SBSN. The Return On Assets (ROA) variable has an asymmetrically significant effect on corporate sukuk but has no effect on SBSN. Meanwhile, in the short term, ROA has a symmetrically significant effect on corporate sukuk and SBSN